1, 2‐migration in N‐phosphano functionalized N‐heterocyclic carbenes. Issue 1 (3rd November 2014) - Kirilchuk, Andrey A.; Yurchenko, Aleksandr A.; Kostyuk, Aleksandr N.; Rozhenko, Alexander B.
<x xml:space="preserve">Abstract</x> 1, 2‐Migration of the phosphano‐group to the carbene center in N‐phosphano functionalized N‐heterocyclic carbenes has been studied by density functional theory (DFT) calculations. An intramolecular mechanism with a three‐center transition state structure seems to be most plausible for the isolated carbenes, while an intermolecular pathway catalyzed by azolium salts may be preferable for a migration proceeding in the course of generating the carbenes in situ. Our calculations show that amino‐substitution at the phosphorus atom and an enhanced nucleophilicity of the heterocycle scaffold facilitate the phosphorus shift. Calculated singlet‐triplet energy gaps do not correlate with thermodynamic stability of the studied carbenes and their disposition toward the 1, 2‐rearrangement. © 2014 Wiley Periodicals, Inc.